2006
DOI: 10.2741/1933
|View full text |Cite
|
Sign up to set email alerts
|

Wnt/frizzled signaling in hepatocellular carcinoma

Abstract: The Wnt/Frizzled (FZD) signaling cascade is important for cell fate determination during embryonic development as well as maintaining tissue homeostasis in the adult. In addition to these physiologic roles, studies have shown that deregulation of Wnt/FZD signaling occurs during carcinogenesis. As an example, over 90% of the colorectal cancers have mutations in adenomatous polyposis coli (APC) or beta-catenin genes. In addition, hepatocellular carcinoma (HCC) is another tumor with frequent aberrant activation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
112
1
2

Year Published

2009
2009
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(118 citation statements)
references
References 121 publications
3
112
1
2
Order By: Relevance
“…Dysregulation of the Wnt signaling pathway is a key molecular lesion in liver cancer (36)(37)(38). More than 60% of liver tumors exhibit accumulation of β-catenin, a hallmark of activated Wnt signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Dysregulation of the Wnt signaling pathway is a key molecular lesion in liver cancer (36)(37)(38). More than 60% of liver tumors exhibit accumulation of β-catenin, a hallmark of activated Wnt signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of the canonical Wnt pathway has been found to be one of the most frequent events associated with the malignant transformation of liver cells [49][50][51][52]. Because GPC3 promotes HCC growth by stimulating canonical Wnt signaling, treatments that target this pathway downstream of this glypican could offer alternative possibilities for blocking its pro-tumorigenic activity.…”
Section: Potential Association With Wnt/3-catenin Therapeuticsmentioning
confidence: 99%
“…Frequent mutations of the β-catenin gene were found in chemically induced colon tumors in both rat and mouse carcinogenesis models (Dashwood et al, 1998;Takahashi et al, 1998;Suzui et al, 1999), suggesting that the APC-β-catenin pathway plays an important role in the development of colon carcinogenesis in rodents, as seen in humans. Recent reports shown that activation of Wnt/β-catenin signaling is important for both initiation and progression of cancers of different tissues/organs, including liver (Lee et al, 2006;Ashokkumar and Sudhandiran, 2011), thus, Wnt/β-catenin signaling pathway is becoming a promising target for chemoprevention and chemotherapy in CRC (Herbst and Kolligs, 2007;Luo et al, 2007;Ashokkumar and Sudhandiran, 2011).…”
Section: 2201 Potential Targets For Prevention Of Colorectal Cancer:mentioning
confidence: 99%